External Validity of the New York University Caregiver Intervention: Key Caregiver Outcomes Across Multiple Demonstration Projects. (September 2019) - Fauth, Elizabeth B.; Jackson, Mark A.; Walberg, Donna K.; Lee, Nancy E.; Easom, Leisa R.; Alston, Gayle; Ramos, Angel; Felten, Kristen; LaRue, Asenath; Mittelman, Mary
Purpose of the Study: The Administration on Aging funded six New York University Caregiver Intervention (NYUCI) demonstration projects, a counseling/support intervention targeting dementia caregivers and families. Three sites (Georgia, Utah, Wisconsin) pooled data to inform external validity in nonresearch settings. This study (a) assesses collective changes over time, and (b) compares outcomes across sites on caregiver burden, depressive symptoms, satisfaction with social support, family conflict, and quality of life.Design and Methods: Data included baseline/preintervention ( N = 294) and follow-up visits (approximately 4, 8, 12 months).Results: Linear mixed models showed that social support satisfaction increased ( p < .05) and family conflict decreased ( p < .05; Cohen's d = 0.49 and 0.35, respectively). Marginally significant findings emerged for quality of life increases ( p = .05) and burden decreases ( p < .10). Depressive symptoms remained stable. Slopes did not differ much by site.Implications: NYUCI demonstrated external validity in nonresearch settings across diverse caregiver samples.